2020
DOI: 10.1002/anie.202008096
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific 1,2‐Migrations of Boronate Complexes Induced by Electrophiles

Abstract: The stereospecific 1,2‐migration of boronate complexes is one of the most representative reactions in boron chemistry. This process has been used extensively to develop powerful methods for asymmetric synthesis, with applications spanning from pharmaceuticals to natural products. Typically, 1,2‐migration of boronate complexes is driven by displacement of an α‐leaving group, oxidation of an α‐boryl radical, or electrophilic activation of an alkenyl boronate complex. The aim of this article is to summarize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 84 publications
(47 reference statements)
0
60
0
Order By: Relevance
“…The diastereoselectivity observed in the synthesis of octahydroindoles 10 and octahydrocyclopenta[ b ]pyrroles 13 can be also rationalized in agreement with the mechanistic proposal, and considering 1) a diastereoselective carboborylation of the diazo compound, [28, 29] 2) a stereoretentive carboborylation of the azide. Retention of configuration on the latter step is expected considering that 1,2‐migrations of boronate complexes are stereospecific and proceed with retention of configuration on the migrating group [17a, 20, 30] . Therefore we propose that the stereochemistry must be defined in the first step.…”
Section: Resultsmentioning
confidence: 93%
“…The diastereoselectivity observed in the synthesis of octahydroindoles 10 and octahydrocyclopenta[ b ]pyrroles 13 can be also rationalized in agreement with the mechanistic proposal, and considering 1) a diastereoselective carboborylation of the diazo compound, [28, 29] 2) a stereoretentive carboborylation of the azide. Retention of configuration on the latter step is expected considering that 1,2‐migrations of boronate complexes are stereospecific and proceed with retention of configuration on the migrating group [17a, 20, 30] . Therefore we propose that the stereochemistry must be defined in the first step.…”
Section: Resultsmentioning
confidence: 93%
“…With these observations in hand, we extended the reaction to a variety of aldehydes and boronic acids (Scheme 3). Keeping 2 a as the reaction partner, we observed that the reaction was very general for the aldehyde counterpart (Scheme 3 a), tolerating other a-hetero functionalized aldehydes (7-9) that included the acid-labile TBSO group (7) and a proline derivative (9) that reacted without epimerization (see SI), [24] 1,2-dicarbonyl derivatives (10, 11), a,b-unsaturated aldehydes (12,13), aliphatic aldehydes (14-16) and aromatic aldehydes (6,(17)(18)(19)(20)(21) including examples with electron-donor substituents (17,18), ortho-substitution (18), and electron-accepting substituents (19)(20)(21). a-Hetero functionalized (4, 7, 8) aldehydes reacted with 2 a at rt allowing the synthesis of the corresponding ketones in good yields.…”
mentioning
confidence: 90%
“…The ability of boronates to engage in migration reactions triggered by the presence of a nearby electrophilic site is one of the most relevant reactions in boron chemistry. [18] In particular, the activation of boronic acids with oxygen nucleophiles permits the transformation of a-hydroxyaldehydes into amines (the Petasis-Mannich reaction). [19] In this reaction, coordination of a vinyl or aryl boronic acid to the hydroxy moiety generates a boronate intermediate that intermolecularly transfers its carbon group to the electrophilic iminium species formed by the interaction of the aldehyde with a primary or secondary amine (Scheme 1 d).…”
mentioning
confidence: 99%
“…With these observations in hand, we extended the reaction to a variety of aldehydes and boronic acids (Scheme 3). Keeping 2 a as the reaction partner, we observed that the reaction was very general for the aldehyde counterpart (Scheme 3 a), tolerating other a-hetero functionalized aldehydes (7)(8)(9) that included the acid-labile TBSO group 7and a proline derivative (9) that reacted without epimerization (see SI), [24] 1,2-dicarbonyl derivatives (10,11), a,b-unsaturated aldehydes (12,13), aliphatic aldehydes (14-16) and aromatic aldehydes (6,(17)(18)(19)(20)(21) including examples with electron-donor substituents (17,18), ortho-substitution 18, and electron-accepting substituents (19)(20)(21). a-Hetero functionalized (4,7,8) aldehydes reacted with 2 a at rt allowing the synthesis of the corresponding ketones in good yields.…”
mentioning
confidence: 98%
“…More hindered (5,9,16) and a,b-unsaturated aldehydes (12,13) also reacted at rt but in moderate yields, which were increased upon heating. However, aromatic aldehydes (6,(17)(18)(19)(20)(21) and 1,2-dicarbonyl derivatives (10,11) required the reaction to be performed at 110 8C. To demonstrate the potential synthetic utility of this methodology, two of the examples (4 and 6) were executed on a 1 g scale with similar yields (see the Supporting Information for details).…”
mentioning
confidence: 99%